Composition of Freshwater Gastropods (Mollusca) in the Midstream of the Cisadane River, West Java, Indonesia - Ridwan, Muhammad; Kadri S, Muh.; Reza Sese, Moh.; Iqram, Muhammad; Priawandiputra, Windra (Universitas Negeri Surabaya, 2025)
Gastropods are important components of freshwater ecosystems, but their diversity and distribution in the Cisadane River, West Java, had not been previously documented. This study investigated the composition and distribution of gastropods at four stations using purposive sampling with 1 × 1 m quadrats. Data were analyzed with the Shannon–Wiener diversity index, Simpson dominance index, Pielou’s evenness index, Kruskal–Wallis test, and ANOSIM to compare community structures among stations, while Spearman’s correlation was applied to examine relationships between species abundance and environmental factors. A total of seven species were recorded: Melanoides tuberculata, Tarebia granifera, Sulcospira testudinaria, Mieniplotia scabra, Clea helena, Radix rubiginosa, and Filopaludina javanica. Station 1 showed the highest diversity (H′ = 1.30) and evenness (E = 0.73), while T. granifera was the most abundant and invasive species. These findings provide the first comprehensive data on freshwater gastropods in the Cisadane River and highlight their potential as bioindicators for conservation and management.